2018
DOI: 10.1016/j.neuropsychologia.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the roles of medial prefrontal and superior temporal cortex in source monitoring

Abstract: Source monitoring, or the ability to recall the origin of information, is a crucial aspect of remembering past experience. One facet of this, reality monitoring, refers to the ability to distinguish between internally generated and externally generated information, biases in which have previously been associated with auditory verbal hallucinations in schizophrenia. Neuroimaging evidence suggests that medial prefrontal and superior temporal (STG) regions may play a role in reality monitoring for auditory verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…This finding suggests that while combinations of different severities of AHs and VHs are related to brain alterations, retinal thickness may be more of a trait marker and not related to symptom severity. This idea is consistent with prior research in first episode un-medicated patients (Bernardin et al 2019;Moseley et al 2018;Thomas 1990). However, contrary to this theory, other studies have reported that retinal thickness and brain GMV reduction are affected by treatment with antipsychotics (Bordier et al 2018;Cao et al 2018;Collier et al 2014;Csaszar et al 2019;Kremlacek et al 2016;Xu et al 2016;Zmigrod et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that while combinations of different severities of AHs and VHs are related to brain alterations, retinal thickness may be more of a trait marker and not related to symptom severity. This idea is consistent with prior research in first episode un-medicated patients (Bernardin et al 2019;Moseley et al 2018;Thomas 1990). However, contrary to this theory, other studies have reported that retinal thickness and brain GMV reduction are affected by treatment with antipsychotics (Bordier et al 2018;Cao et al 2018;Collier et al 2014;Csaszar et al 2019;Kremlacek et al 2016;Xu et al 2016;Zmigrod et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the study was designed to assess the effects that were specific to the sensory modality involved in hallucinations, i.e., AH or V + AH, rather than the effects that were more broadly related to schizophrenia and medication. Fourth, although the task used to measure reality-monitoring processes in our study was similar to the paradigms that have been previously used to assess reality-monitoring, with imagined and heard words presented visually [13, 3638], this task came with some limitations. Indeed, we cannot exclude that participants may not have always followed the instruction to imagine hearing the visually presented words and that it could have affected their performance during the retrieval phase.…”
Section: Discussionmentioning
confidence: 99%
“…The task was based on previously used versions (e.g., Moseley et al, 2018), though differed from others in a number of ways to ensure consistency across data collection sites and online.…”
Section: Source Memory Task (Smt)mentioning
confidence: 99%